Sex-specific changes in protein expression of membrane transporters in the brain cortex of 5xFAD mouse model of Alzheimer's disease - Elena Puris; Liudmila Saveleva; Seppo Auriola; Mikko Gynther; Katja M. Kanninen; Gert Fricker (Frontiers Media S.A., 2024)
Membrane transporters playing an important role in the passage of drugs, metabolites and nutrients across the membranes of the brain cells have been shown to be involved in pathogenesis of Alzheimer's disease (AD). However, little is known about sex-specific changes in transporter protein expression at the brain in AD. Here, we investigated sex-specific alterations in protein expression of three ATP-binding cassette (ABC) and five solute carriers (SLC) transporters in the prefrontal cortex of a commonly used model of familial AD (FAD), 5xFAD mice. Sensitive liquid chromatography tandem mass spectrometry-based quantitative targeted absolute proteomic analysis was applied for absolute quantification of transporter protein expression. We compared the changes in transporter protein expressions in 7-month-old male and female 5xFAD mice versus sex-matched wild-type mice. The study revealed a significant sex-specific increase in protein expression of ABCC1 (p = 0.007) only in male 5xFAD mice as compared to sex-matched wild-type animals. In addition, the increased protein expression of glucose transporter 1 (p = 0.01), 4F2 cell-surface antigen heavy chain (p = 0.01) and long-chain fatty acid transport protein 1 (p = 0.02) were found only in female 5xFAD mice as compared to sex-matched wild-type animals. Finally, protein expression of alanine/serine/cysteine/threonine transporter 1 was upregulated in both male (p = 0.02) and female (p = 0.002) 5xFAD mice. The study provides important information about sex-specific changes in brain cortical transporter expression in 5xFAD mice, which will facilitate drug development of therapeutic strategies for AD targeting these transporters and drug delivery research.